Analysis of Characteristics of Volatile Organic Compounds Pollution in Atmosphere in Kuitun City and Countermeasures. Issue 1 (January 2021) - Wang, Linna; Yang, Rongjiang; Men, Chunyan; Gao, Li
Abstract: The "Kui-Du-Wu" area of Kuitun City is one of the largest petrochemical bases and important economic core areas in Xinjiang. According to the online monitoring data of total volatile organic compounds (VOCs) at Kuitun site, 102 species can be detected in the urban atmospheric environment volatile organic compounds, through the analysis of the sources of the top ten compounds with average concentration values throughout the year, their main sources are chemical production, oil volatilization, fuel combustion, and motor vehicle exhaust. The prevention and control countermeasures are to strengthen source control, implement pollution source compliance management, improve the city's comprehensive management level, and establish and improve a joint prevention and control system.